The Relationship Between Intensity of Pain With Sleep Quality in Patients With Gout Desease - Maria Haryanti Butarbutar; Srilasmawanti Srilasmawanti; Arief Rahman; Khairul Fadly (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Gout is a clinical syndrome resulting from the deposition of urine (monosodium urate monohydrate) crystals. The crystals may be deposited in a joint, leading to an acute inflammatory response, or in soft tissues, such as cartilage, causing no inflammation. Most cases of gout are characterized by the sudden onset of severe acute monarticular arthritis in a peripheral joint in the leg. The arthritis remits completely and then recurs with increasing frequency. After approximately 10 years of recurrent gouty arthritis, tophi develop in cartilage, tendons, and bursae in some patients.. The purpose of research To know the relationship between the intensity of pain with sleep quality in patients with Rheumatoid Arthritis in elderly Patients with Rheumatoid Arthritis in Dusun II Desa Helvetia Medan. The research design used survey analytic cross-sectional methods. The sampling technique used total sampling, the Sample size of 60 respondents. The Data were obtained using a questionnaire VASE-cope containing 20 items of questions, the data analysis used is univariate and bivariate. Based on the Analysis results with the Results of using the test chi-square test showed that the significant value of the probability (Asymp. Sing) The Intensity of Pain is .0,003 <value sing ? of 0.05, it was proved that there was a relationship of Pain Intensity with the quality of sleep in elderly patients with Gout in Dusun II Desa Helvetia. The conclusion in this study showed that statistically there is a relationship between Pain Intensity and sleep quality in elderly patients with Gout Helvetia Village.. Elderly people know more about Pain Intensity and can control sleep well.